Treatment of Colorectal Cancer - Rawls, George H. (1982)
Carcinoma of the colorectum should be suspected and diagnosed early and treated adequately. Principles of surgical therapy are discussed. Meticulous follow-up is essential and re-exploration to remove recurrent disease is necessary.